A Simple Technique for Rapid Assessment of Rat (Rattus norvegicus) Sperm Motility - Muhammad Ja'far Luthfi; Mahanem Mat Noor (Biology, Medicine, & Natural Product Chemistry, 2020)
Assesment of rat sperm motility can be carried out on sperm sample from epididimal source using minimal amount of equipment. This method will aid researcher and practitioner working in the field of sperm quality to determined rat sperm  motility rapidly and efficiently.